Microsatellite Alterations with Allelic Loss at 9p24.2 Signify Less-aggressive Colorectal Cancer Metastasis - Koi, Minoru (Gastroenterology, 2016)
BACKGROUND & AIMS: Molecular events that lead to recurrence and/or metastasis after curative treatment of patients with colorectal cancers (CRCs) are poorly understood. Patients with stage II or III primary CRC with increased numbers of microsatellite alterations at selected tetra-nucleotide repeats (EMAST) and low levels of microsatellite instability (E/L) are more likely to have disease recurrence after treatment. Hypoxia and/or inflammation not only promote metastasis but also induce EMAST by causing deficiency of MSH3 in the cancer cell nucleus. We aimed to identify genetic alterations associated with metastasis of primary colorectal tumors to liver and to determine their effects on survival. METHODS: We obtained 4 sets of primary colorectal tumors and matched liver metastases from hospitals in Korea and Japan. Intragenic microsatellites with large repeats at 141 loci were examined for frame-shift mutations and/or loss of heterozygosity (LOH) as possible consequences of MSH3 deficiency. Highly altered loci were examined for association with E/L in liver metastases. We analyzed data from 156 of the patients with stage II or III primary colorectal tumors to determine outcomes and whether altered loci were associated with E/L. RESULTS: LOH at several loci at chromosome 9p24.2 (9p24.2-LOH) was associated with E/L in liver metastases (odds ratio, 10.5; 95% confidence interval [CI], 2.69–40.80; P=.0007). We found no significant difference in the frequency of E/L, 9p24.2-LOH, mutations in KRAS or BRAF, or the combination of E/L and 9p24.2-LOH between primary colorectal tumors and their matched metastases. Patients with stage II or III colorectal tumors with E/L and 9p24.2-LOH had increased survival following CRC recurrence (hazard ratio, 0.25; 95% CI, 0.12–0.50; P=.0001), compared to patients without with E/L and 9p24.2-LOH. E/L with 9p24.2-LOH appeared to be an independent prognostic factor for overall survival of patients with stage III CRC (hazard ratio, 0.06; 95% CI, 0.01–0.57; P=.01). CONCLUSIONS: E/L with 9p24-LOH appears to be a biomarker for less aggressive metastasis from stage III primary colorectal tumors.